184k views
5 votes
Vertex = (2,5), Point (0, 1)

1 Answer

2 votes

Answer:

therefore y= - (x-2)^2 + 5

Explanation:

u do this by using this format here ..,

y=a(x-h)^2+k

sub in the vertex points as h=2 and k = 5 , since the 2 is positive its sign will be -2 in the brackets because when solving for x-2=0 it is x=2

y=a(x-2)^2+5

then with your (0,1) points plug that in as y and x

1=a(0-2)^2+5

1=a(-2)^2+5

1=4a+5

1-5=4a

-4=4a

a=-1

therefore y= - (x-2)^2 + 5

User Ilio Catallo
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.